On R0 Space in L-Topological Spaces (Journal of Bangladesh Academy of Sciences, 2016)
R0 space in L-topological spaces are defined and studied. The authors give eight definitions of R0 space in L-topological spaces and discuss certain relationship among them. They showed that all of these satisfy good extension property. Moreover, some of their other properties are obtained.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 117-124, 2016